Lamarckian evolution of the giant Mimivirus in allopatric laboratory culture on amoebae - Colson, Philippe; Raoult, Didier (Frontiers in Cellular and Infection Microbiology, 2012)
Acanthamoeba polyphaga Mimivirus has been subcultured 150 times on germ-free amoebae. This allopatric niche is very different from that found in the natural environment, where the virus is in competition with many other organisms. In this experiment, substantial gene variability and loss occurred concurrently with the emergence of phenotypically different viruses. We sought to quantify the respective roles of Lamarckian and Darwinian evolution during this experiment. We postulated that the Mimivirus genes that were down-regulated at the beginning of the allopatric laboratory culture and inactivated after 150 passages experienced Lamarckian evolution because phenotypic modifications preceded genotypic modifications, whereas we considered that genes that were highly transcribed in the new niche but were later inactivated obeyed Darwinian rules. We used the total transcript abundances and sequences described for the genes of Mimivirus at the beginning of its laboratory life and after 150 passages in allopatric culture on Acanthamoeba spp. We found a statistically significant positive correlation between the level of gene expression at the beginning of the culture and gene inactivation during the 150 passages. In particular, the mean transcript abundance at baseline was significantly lower for inactivated genes than for unchanged genes (165±589 vs. 470±1,625; p<1e-3), and the mean transcript levels during the replication cycle of Mimivirus M1 were up to 8.5-fold lower for inactivated genes than for unchanged genes. In addition, proteins tended to be less frequently identified from purified virions in their early life in allopatric laboratory culture if they were encoded by variable genes than if they were encoded by conserved genes (9% vs. 15%; p= 0.062). Finally, Lamarckian evolution represented the evolutionary process encountered by 63% of the inactivated genes. Such observations may be explained by the lower level of DNA repair of useless genes.